Evaluation of orange-fleshed sweetpotato genotypes for root yield and yield-related traits in South and Northern parts of Ethiopia - Fekadu Gurmu; Bililign Mekonnen; Birehanu Habete (Cogent Food & Agriculture)
Orange-fleshed sweetpotato (OFSP) is a crop with the potential to significantly contribute to the food systems of farming communities. The evaluation of OFSP genotypes in a multi-environment trial is critical for identifying the best genotype with high yield potential and recommending it for wider-scale production. Ten OFSP genotypes were evaluated in three locations in the southern and northern parts of the country, namely Hawassa, Dilla, and Fogera, for two consecutive years (2021 and 2022), with the objective of identifying the best genotypes for root yield, root dry matter (DMC), and beta-carotene contents (BCC), including sweetpotato virus disease (SPVD) response. Data were recorded on root yield, SPVD, DMC, BCC, and other traits (root length, root girth, above-ground biomass). The result showed the presence of a highly significant (p < .001) difference among genotypes and the test locations, indicating a differential response of genotypes across locations. Among the tested genotypes, genotype G8 (Cacilia-22) outperformed the others across locations over years in terms of root yield, DMC, and BCC, with yield advantages of 23.68%, 6.67%, and 20.53%, respectively. It was also confirmed by the genotype plus genotype by environment interaction (GGE) biplot that the genotype with the best performance was G8. It also showed stable performance across test locations. Moreover, G8 showed a low SPVD reaction score of 1.17 to SPVD reaction on a scale of 1 to 9; scores below 3.0 suggest that it falls within the resistance range. Therefore, G8 (Cacilia-22) can be recommended for verification and release for wider production in Ethiopia.